The economy and party preferences in multi-level systems: the influence of economic perceptions and partisan congruence in six regions - Toubeau, Simon; Wagner, Markus (Elsevier, 2018)
How does the economy influence party preferences in multi-level states? Using regional-level survey data from Canada, Germany and Spain, we show that there is a ‘cross-level’ effect of economic evaluations. Citizens thus take into consideration both the regional and the national economy when determining their support for incumbents at either level. However, the way in which they do so depends on whether the same party is in office at two levels or not. If so, standard reward-punishment patterns apply. If different parties are in office at the two levels, incumbents at one level are rewarded for bad and punished for good economic outcomes at the other level. Overall, the influence of cross-level economic perceptions is about half as large as that of same-level economic perceptions. Our findings have important normative implications for the signalling function of elections.